(untitled) (Revista de Ensino em Artes, Moda e Design, 2026)
Editorial of the Dossier: A delicate absurdity: Teaching, Humor, Creation and Complex Thought with/in Gianni Rodari and Edgar Morin" with a preamble on the theme, the thinkers discussed and summaries of the published contributions.